- #1

- 533

- 1

[tex]

e^{1/z} + \frac{1}{1-e^{1/z}} = w.

[/tex]

How in the world should I go about doing that?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter AxiomOfChoice
- Start date

- #1

- 533

- 1

[tex]

e^{1/z} + \frac{1}{1-e^{1/z}} = w.

[/tex]

How in the world should I go about doing that?

- #2

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 964

[tex]u+ \frac{1}{1- u}= w[/tex]

Multiply both sides by 1- u to get u(1- u)+ 1= w(1- u) or [itex]u- u^2+ 1= w- uw[/itex] which equivalent to the quadratic equation [itex]u^2- (1+w)u+ w-1= 0[/itex]. Use the quadratic formula to solve that, then solve [itex]e^{1/z}= u[/math] by taking the logarithm of both sides.

- #3

- 533

- 1

[tex]u+ \frac{1}{1- u}= w[/tex]

Multiply both sides by 1- u to get u(1- u)+ 1= w(1- u) or [itex]u- u^2+ 1= w- uw[/itex] which equivalent to the quadratic equation [itex]u^2- (1+w)u+ w-1= 0[/itex]. Use the quadratic formula to solve that, then solve [itex]e^{1/z}= u[/math] by taking the logarithm of both sides.

Great. Thanks. This was my original approach, but for some reason I wasn't sure if I could make that change of variables and apply the quadratic formula like you did. But you've confirmed my intuition, so I'm going with it!

Share: